Endogenous vitamin E metabolites mediate allosteric PPARγ activation with unprecedented co-regulatory interactions. Issue 10 (21st October 2021) - Willems, Sabine; Gellrich, Leonie; Chaikuad, Apirat; Kluge, Stefan; Werz, Oliver; Heering, Jan; Knapp, Stefan; Lorkowski, Stefan; Schubert-Zsilavecz, Manfred; Merk, Daniel
Summary: Vitamin E exhibits pharmacological effects beyond established antioxidant activity suggesting involvement of unidentified mechanisms. Here, we characterize endogenously formed tocopherol carboxylates and the vitamin E mimetic garcinoic acid (GA) as activators of the peroxisome proliferator-activated receptor gamma (PPARγ). Co-stimulation of PPARγ with GA and the orthosteric agonist pioglitazone resulted in additive transcriptional activity. In line with this, the PPARγ-GA complex adopted a fully active conformation and interestingly contained two bound GA molecules with one at an allosteric site. A co-regulator interaction scan demonstrated an unanticipated co-factor recruitment profile for GA-bound PPARγ compared with canonical PPARγ agonists and gene expression analysis revealed different effects of GA and pioglitazone on PPAR signaling in hepatocytes. These observations reveal allosteric mechanisms of PPARγ modulation as an alternative avenue to PPARγ targeting and suggest contributions of PPARγ activation by α-13-tocopherolcarboxylate to the pharmacological effects of vitamin E. Graphical abstract: Highlights: Garcinoic acid and tocopherol carboxylates are natural PPARγ ligands Garcinoic acid binds to the orthosteric and an allosteric PPARγ ligand binding site Garcinoic acid and pioglitazone induce different PPARγ-co-regulator interactions Garcinoic acid and pioglitazone have different effects on gene expression profiles Abstract : Garcinoic acid (GA) structurally mimics tocopherol carboxylates that are endogenously formed metabolites of vitamin E. Willems et al. characterize GA as a ligand of the transcription factor PPARγ with distinctive binding and modulatory properties pointing to an involvement of PPARγ modulation in the pharmacological actions of vitamin E.